ANALISIS PENGARUH PELAYANAN TERHADAP TINGKAT KEPUASAN KONSUMEN DALAM BERBELANJA DI ALFAMART BREBES - Nasroni, Slamet (PERMANA, 2014)
This study discusses the effect of service to customer satisfaction in the shop Alfamart in Brebes. The expected goals of this research is to determine whether the service has an influence on customer satisfaction in the shop Alfamart in Brebes and to determine how much influence the service for customer satisfaction in the shop Alfamart in Brebes. Results of research conducted that calculation results rho Spearman rank correlation between service and customer satisfaction Alfamart Brebes is equal to 0,838. Which means the correlation between the service to customer satisfaction is very strong. The strength of this effect can be seen in the determination coefficient 0,722 or 72,2 percent. This means that 72.2 percent customer satisfaction Alfamart Brebes affected by the service. This can be proved by using the t test using a 95 percent confidence level (Î± = 0.05) and degrees of freedom N-2 (100-2) obtained t table 1658 and the results of calculations in SPSS showed 15 965 which means that t count > t table. This shows that Ho is rejected or services significantly affect customer satisfaction Alfamart Brebes. To determine the effect of service to customer satisfaction Alfamart Brebes, then used simple regression analysis tool with the formula Y = a + bx is Y = 10 320 + 0,798x. From this equation can be explained that the constant value 10 320 which means that if the variable is ignored then service customer satisfaction Alfamart Brebes only amounted to 10 320 units. While in the service variable (X) is obtained if the variable value 0798 means that the service is increased by one unit then Alfamart Brebes customer satisfaction will increase by 0798 units of time.This study discusses the effect of service to customer satisfaction in the shop Alfamart inBrebes. The expected goals of this research is to determine whether the service has aninfluence on customer satisfaction in the shop Alfamart in Brebes and to determine howmuch influence the service for customer satisfaction in the shop Alfamart in Brebes.Results of research conducted that calculation results rho Spearman rank correlationbetween service and customer satisfaction Alfamart Brebes is equal to 0,838. Whichmeans the correlation between the service to customer satisfaction is very strong. Thestrength of this effect can be seen in the determination coefficient 0,722 or 72,2percent. This means that 72.2 percent customer satisfaction Alfamart Brebes affected bythe service. This can be proved by using the t test using a 95 percent confidence level (Î±= 0.05) and degrees of freedom N-2 (100-2) obtained t table 1658 and the results ofcalculations in SPSS showed 15 965 which means that t count > t table. This shows that Hois rejected or services significantly affect customer satisfaction Alfamart Brebes. Todetermine the effect of service to customer satisfaction Alfamart Brebes, then usedsimple regression analysis tool with the formula Y = a + bx is Y = 10 320 + 0,798x.From this equation can be explained that the constant value 10 320 which means that ifthe variable is ignored then service customer satisfaction Alfamart Brebes onlyamounted to 10 320 units. While in the service variable (X) is obtained if the variablevalue 0798 means that the service is increased by one unit then Alfamart Brebescustomer satisfaction will increase by 0798 units of time.